Participation Makes A Difference : But Not Always How and Where We Might Expect - Gabonventa, John (2012)
In their article: Participatory Development Revisited, Ghazala Mansuri and Vijayendra Rao outline the high hopes for participation over the last two decades, yet conclude that participatory development has become a "tarnished silver bullet," perhaps another in a long series of development fads that promise more than they deliver.